Assessment of Efficiency and Safety of Apatinib in Advanced Bone and Soft Tissue Sarcomas: A Systematic Review and Meta-Analysis - Long, Zuoyao; Huang, Mengquan; Liu, Kaituo; Li, Minghui; Li, Jing; Zhang, Hongmei; Wang, Zhen; Lu, Yajie (Frontiers in Oncology, 2021)
Background: Previous studies, both in vitro and in vivo, have established that apatinib has anti-tumor properties. However, insufficient empirical evidence of the efficacy and safety of apatinib has been published for bone and soft tissue sarcoma, the reported results differing widely. Here, we conducted a meta-analysis to assess the efficacy and toxicity of apatinib for the treatment of bone and soft tissue sarcoma. Methods: Pubmed, Medline, Web of Science, ScienceDirect, Ovid, Embase, Cochrane Library, Scopus, Vip (China), Cnki (China), Wanfang (China), and CBM (China) databases and literature from conferences were searched for studies of apatinib for the treatment of bone and soft tissue sarcomas, published from the inception of each database to Sep 1, 2020, without language restrictions. Primary outcomes were efficacy and toxicity of apatinib for the treatment of bone and soft tissue sarcoma, including treatment response, progression-free survival (PFS), and the incidence of adverse events. After extraction of data and methodological quality evaluation, random or fixed-effects models, as appropriate, were selected to calculate pooled effect estimates using R software (Version 3.4.1). Results: A total of 21 studies with 827 participants were included in the present meta-analysis. The mean MINORS score was 10.48±1.75 (range: 7-13), indicating evidence of moderate quality. Pooled outcomes indicated that overall response rate (ORR) and disease control rate (DCR) were 23.85% (95% CI: 18.47%-30.21%) and 79.16% (95% CI: 73.38%-83.68%), respectively. Median PFS ranged from 3.5 to 13.1 months, with a mean of 7.08±2.98 months. Furthermore, the rates of PFS (PFR) after 1, 6, and 12 months were 99.31%, 44.90%, and 14.31%, respectively. Drug-related toxicity appears to be common in patients administered apatinib, for which hand-foot syndrome (41.13%), hypertension (36.15%), and fatigue (20.52%) ranked the top three most common adverse events. However, the incidence of grade 3-4 adverse events was relatively low and manageable. Conclusions: Based on the best evidence currently available, apatinib demonstrates promising clinical efficacy and an acceptable safety profile for the treatment of advanced bone and soft tissue sarcoma, although additional high-quality clinical studies are required to further define its properties and toxicity.